Isolation and analysis of components of CD95 (APO-1/Fas) death-inducing signaling complex - Watzl, Carsten; Krammer, Peter H.; Peter, Marcus E. (Methods, 2002)
CD95 (APO-1/Fas) is an apoptosis-inducing receptor belonging to the tumor necrosis factor receptor superfamily. Multimerization of CD95 leads to instant recruitment of the signaling molecules FADD and caspase-8 to the activated receptor forming the death-inducing signaling complex (DISC). DISC formation is the first essential step of CD95 signaling and results in activation of caspase-8 starting a signaling cascade that leads to apoptosis. Here we describe a method for analyzing the CD95 DISC. The method is based on coimmunoprecipitation of the signaling molecules with the activated CD95 receptor followed by Western blot detection of associated molecules. Therefore, this method can analyze the very first signaling events during CD95-mediated apoptosis.
Available online 25 May 2002
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 03.03.2021